Increasing temperature and time in glasshouses increases honey bee activity and affects internal brood conditions - Darren P. O'Connell; Bronte M. Baker; David Atauri; Julia C. Jones (Journal of Insect Physiology, 2024)

Spatially explicit estimates of N 2 O emissions from croplands suggest climate mitigation opportunities from improved fertilizer management - James S. Gerber; Kimberly M. Carlson; David Makowski; Nathaniel D. Mueller; Iñaki Garcia de Cortazar‐Atauri; Petr Havlík; Mario Herrero; Marie Launay; Christine S. O'Connell; Pete Smith; Paul C. West (Global Change Biology, 2016)
With increasing nitrogen (N) application to croplands required to support growing food demand, mitigating N 2 O emissions from agricultural soils is a global challenge. National greenhouse gas emissions accounting typically estimates N 2 O emissions at the country scale by aggregating all crops, under the assumption that N 2 O emissions are linearly related to N application. However, field studies and meta‐analyses indicate a nonlinear relationship, in which N 2 O emissions are relatively greater at higher N application rates. Here, we apply a super‐linear emissions response model to crop‐specific, spatially explicit synthetic N fertilizer and manure N inputs to provide subnational accounting of global N 2 O emissions from croplands. We estimate 0.66 Tg of N 2 O‐N direct global emissions circa 2000, with 50% of emissions concentrated in 13% of harvested area. Compared to estimates from the IPCC Tier 1 linear model, our updated N 2 O emissions range from 20% to 40% lower throughout sub‐Saharan Africa and Eastern Europe, to >120% greater in some Western European countries. At low N application rates, the weak nonlinear response of N 2 O emissions suggests that relatively large increases in N fertilizer application would generate relatively small increases in N 2 O emissions. As aggregated fertilizer data generate underestimation bias in nonlinear models, high‐resolution N application data are critical to support accurate N 2 O emissions estimates.